PENGUJIAN PROPERTI PSIKOMETRIK INTELLIGENZ STRUKTUR TEST SUBTES KEMAMPUAN SPASIAL DUA DIMENSI (FORM AUSWAHL): STUDI PADA DUA SMA SWASTA DI JAKARTA - Indro Adinugroho (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2016)
Intelligenz Struktur Test (IST) is one-kind psychological measurement that has primary function measure human intelligence. As an intelligence test, IST produces mean score in the context of human ability called intelligence quotient (IQ). IST was developed by Rudolf Amthauer on 1953 in Germany, also with Primary Mental Abilities (PMA) as its theoretical framework. PMA is a basic concept of intelligence developed by Lois Leon Thurstone that describes seven primary abilities exists in human cognition. Until now, IST is still used in Psychological Services Bureau (PSB), Faculty of Psychology Atma Jaya Catholic University as their primary tool for assessment and evaluation purposes. This study aims to examine the psychometric properties of one of the subtest in IST that measures two-dimension spatial intelligence, Form Auswahl (FA). Techniques related to psychometric examination will include item analysis, convergent and discriminant validation and also split-half method for reliability testing. Item analysis shows the empirical support to retain all the items in FA. However, distractor-analysis shows different result. There is a need to revise some of the choices due to lack of capability to flam the answer of lower group. In conclusion, validity and reliability examinations show that FA is still appropriate for assessing two-dimension spatial ability in Indonesian context.